FOOD CONTACT SURFACE CONTAMINANTS: A REVIEW - Mohammed Rufai, Suwaiba; Wartu, Joseph Reuben (FUDMA JOURNAL OF SCIENCES, 2024)
Food contact surfaces are major sources of food contamination. They harbour contaminants which are further transferred to the food that comes in contact with them. These contaminants could be of biological or chemical origin. The biological contaminants are microorganisms such as Staphylococcus aureus, Campylobacter spp, Escherichia coli, Shigella spp, Salmonella spp, Listeria monocytogenes, Vibrio cholerae, Bacillus cereus, norovirus, hepatitis A virus, etc. The chemical contaminants are chemicals that may be transferred to the food through food contact materials such as packaging materials or residues of cleaning agents. These chemicals are hazardous to human health. Both the biological and chemical contaminants are harmful to humans when consumed. As such, food contact surfaces should be cleaned and sanitized properly to avoid contaminating food with such contaminants and also to ensure that safe food is supplied to the public.
Keywords: food contact; contamination; human health